Türk siyasi partilerinin dış politika yaklaşımları (1961-1971) - Cavlan, Turan (My University, 2008)
TÜRK SİYASÎ PARTİLERİNİN DIŞ POLİTİKA YAKLAŞIMLARI (1961-1971) Bu çalışmada 27 Mayıs 1960 askerî darbesinden sonra seçilerek Türkiye Büyük Millet Meclisi’ne girebilmiş partilerin Türk dış politikasına yaklaşımları ele alınmıştır. Bunun için de ilk bölümde Batı Avrupa’da ortaya çıkan siyasî partilerin gelişimi, türleri ve işlevleri araştırılmıştır. İkinci bölümde 27 Mayıs darbesinden sonra kabul edilmiş 1961 Anayasası, dış politika yapım süreci, darbeden önce varolan Cumhuriyet Halk Partisi ile darbe sonrasında kurulmuş partilerin ideolojik yapılarıyla genel dış politika görüşleri ve genel seçimler ele alınmıştır. Üçüncü bölümde ise Türk dış politikasını ilgilendiren olaylar ve TBMM’ye girebilen partilerin bu olaylara bakış tarzları, olaylar hakkındaki görüşleri ve sözcülerin parti görüşlerini yansıtmaları irdelenmiştir.

FOREIGN POLICY APPROACHES OF TURKISH POLITICAL PARTIES (1961-1971) In this study, it was taken up the approaches of political parties that could form groups in Turkish Grand National Assembly (TGNA). To do so, in the first chapter, the historical development of political parties, which has been first established in the Western Europe, types and fuctions of parties has been searched. In the second chapter, 1961 Constitution that had been accepted after the May 27, 1960 military intervention and the new -with the exception of the Republican Peoples Party; RPP/ CHP- political parties’ ideological structures, governments established after 1961 and general foreign policy approaches were taken into consideration.In the third chapter, events related with the Turkish foreign relations and the perspectives and the thoughts that were stated by party spokesmen parties’ of political parties, which could have the right to be represented in the TGNA, are studied.
Keywords: 27 Mayıs Askeri Darbesi; Siyasi Partiler_Türkiye; Türkiye_Dış İlişkiler